STRATEGI PEMERINTAH KABUPATEN WONOGIRI DALAM MENGEMBANGKAN SENTRA AGROINDUSTRI BREM PUTIH - Mohamad Harisudin; Arip Wijianto; Widiyanto Widiyanto (Universitas Sebelas Maret, 2012)
This study aims to analyze condition of white brem agroindustrial center inWonogiri, Identifying internal and external environmental conditions, Determiningalternative strategies and priorities determining the most appropriate strategy appliedWonogiri Government in developing agro-industry white brem centers. This study is adescriptive analytical study using primary and secondary data. Primary data to explain thewhite brem conditions agroindustry, strategic factors and alternative strategies anddetermination of the strategy through surveys, observation and focus group discussion.Secondary data in the form of monographs and the potential economic data in Wonogiriregency. Tools Analysis used is the SWOT matrix and the matrix QSP. The studyconcluded that the centers of agroindustrial white brem in Wonogiri is the average revenuein May 2011 amounted to Rp 17,634,375, -; cost needed is Rp 16,103,678, - and therevenue of Rp 1,530,697, -. Strength strategic factors are ease of exchanging information,ease of making sales of products, experience and skills sought a long labor. Strategicfactors are drawbacks: The employers are less innovative, less promotional efforts, piecesof white brem uninteresting, unattractive packaging, the center has not been managed well,the strategic factor market opportunities is a high demand, the development of servicesuppliers of raw materials, the presence of community agencies (bakul), alignments ofgovernment policies, developments in food processing technology, development ofinformation technology. Strategic factor is the threat of price fluctuations of raw materials,competitors' similar product innovation, the presence of product substitution, governmentpolicies that are less integrated, bright sun /weather. Priority strategies are recommended sothat the development of agro-industry centers in the white brem Wonogiri can runeffectively is to Improve togetherness among employers to boost innovation in order toincrease profits.